Addressing unwarranted variation in clinical cancer practice - Menon, M (2017)
In the clinical setting, the term 'unwarranted variation' refers to variations in patient outcomes that cannot be explained by the patient's illness or medical needs, or the dictates of evidence-based medicine. These variations persist even after adjusting for patient-related factors. Unwarranted variation depends on a mix of disparities, including inequalities in access to appropriate care in a wide variety of geographical and cultural settings, in the uptake and application of clinical knowledge, in the prioritisation and allocation of resources, and differences in organisational and professional culture. Nevertheless unwarranted variation has been inexorably linked with clinical practice. The Multidisciplinary team (MDT) is an important component of cancer care and is analysed as one of the two strands of clinical practice. Temporal trends in colorectal cancer care, resource utilisation and MDT workings are analysed using mix-method approaches. Colorectal cancer and Liver MDTs in Oxford and Gothenburg were observed and its members interviewed. The framework on unwarranted variation is reviewed with the view of assessing its utility in colorectal cancer care while the implication Cancer Drug Fund has on variation in clinical practice is also explored. Results indicate significant mortality amongst the elderly with colorectal cancer and a significant number of patients not receiving surgery within oneyear of diagnosis. However 90-day post surgical mortality has improved. No association between colorectal cancer spend and patient outcomes were found. Members of MDTs were observed to have diverse views on the roles and responsibilities of their MDT. Potential antecedents to unwarranted variation were identified through MDT workings. This study makes a distinction between professional uncertainty and clinical uncertainty to address the potential source of unwarranted variation. Recommendations on issues MDTs need to address such as defining its core purpose and developing reporting standards are made. A modification to the definition of unwarranted variation is also suggested. This study also proposes a conceptual risk scoring approach based on clinical pathways for addressing unwarranted variation. Several research areas have also been suggested.